2015
DOI: 10.1002/biot.201400577
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the NADH pool and NADH/NADPH ratio redistributes acetoin and 2,3‐butanediol proportion in Bacillus subtilis

Abstract: Bacillus subtilis produces acetoin as a major product along with several NADH-dependent byproducts, especially 2,3-butanediol. In this study, the down-regulation of the NADH pool and the redistribution of NADH/NADPH were targeted using external and genetic processes, as a means by which to redistribute the metabolic flux in favor of acetoin synthesis. First, it was found that the use of carbon sources of different oxidation states resulted in very different intracellular NADH/NAD(+) ratios that dictated the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 32 publications
3
31
1
Order By: Relevance
“…We observed that as soon as glucose had been depleted, R-BDO was oxidized, and this probably provided the NADH needed for NOX to maintain a reduced intracellular environment and thereby prevent unnecessary oxidative stress. 2,3-BDO oxidation upon substrate exhaustion has also been observed in previous studies37.…”
Section: Discussionsupporting
confidence: 83%
“…We observed that as soon as glucose had been depleted, R-BDO was oxidized, and this probably provided the NADH needed for NOX to maintain a reduced intracellular environment and thereby prevent unnecessary oxidative stress. 2,3-BDO oxidation upon substrate exhaustion has also been observed in previous studies37.…”
Section: Discussionsupporting
confidence: 83%
“…The gene gdh with the upstream region including Hpa II promoter was amplified using forward primer P 1 and reverse primer P 2 using pMA5‐ gdh as template . The amplified gene was first inserted into simple cloning vector pMD18T TaKaRa Co. (Dalian, China)) by T4 ligase enzyme under the control of Hpa II promoter, forming to pMD18T‐ Hpa II ‐gdh .…”
Section: Methodsmentioning
confidence: 99%
“…Acetoin, which occurs naturally in corn, grapes, cocoa, apples, butter, coffee, and beer, is a famous flavor agent. During production of acetoin, several NADH‐dependent byproducts always appear, especially 2,3‐butanediol (2,3‐BDL) . Some strategies, e.g.…”
Section: Introductionmentioning
confidence: 99%